Maternal death by cancer in pregnancy: A descriptive study of the International Network on Cancer, Infertility and Pregnancy - Heimovaara, Joosje H; Huis In 't Veld, Evangeline A; Lok, Christianne A R; Garcia, Alvaro Cabrera; Halaska, Michael J; Boere, Ingrid; Gziri, Mina Mhallem; Fruscio, Robert; Painter, Rebecca C; Cardonick, Elyce; van den Heuvel-Eibrink, Marry M; Masturzo, B; et al. (BJOG, 2024)
OBJECTIVE: To characterise pregnant women diagnosed with primary or recurrent cancer who died during pregnancy, during delivery or within 1 year postpartum. DESIGN: A descriptive study. SETTING: The registry of the International Network on Cancer, Infertility and Pregnancy (INCIP). POPULATION: Women diagnosed with cancer during pregnancy between 2000 and 2022. METHODS: Using the INCIP registry database, we compared the characteristics of all women with cancer who died during pregnancy, delivery or within 1 year postpartum with those of all women with cancer who survived the first year postpartum. MAIN OUTCOME MEASURES: Maternal and tumour characteristics and obstetrical and neonatal outcomes. RESULTS: Of the 2359 women registered in INCIP, there were 131 cases (5.6%) of maternal mortality. Lung cancer (9/14, 64.3% of all registered women with lung cancer), gastro-oesophageal cancer (13/21, 61.9%) and acute leukaemia (17/105, 16.2%) had the highest rates of maternal mortality. Maternal mortality was associated with fewer live births compared with the control group without maternal mortality (99/131, 75.6%, vs 1952/2163, 90.0%; P < 0.001), more elective caesarean sections (64/104, 60.4%, vs 756/1836, 41.2%; P < 0.001) and a lower gestational age at (induced) delivery (34.0 vs 37.1 weeks; P < 0.001), resulting in more preterm births. CONCLUSIONS: Maternal mortality occurred in 5.6% of cancer-in-pregnancy cases and is associated with adverse perinatal outcomes.
Keywords: mateřská mortalita; Registries; novorozenec; Infant, Newborn; smrt matky; výsledek těhotenství; Pregnancy; Humans; cancer in pregnancy; registrace; Female; dospělí; Pregnancy Outcome; lidé; cancer‐related maternal death; Adult; ženské pohlaví; Maternal Mortality; těhotenství; Neoplasms; Maternal Death; nádorové komplikace v těhotenství; nádory; Pregnancy Complications, Neoplastic